Reading Fluency Measurements in EFA FTI Partner Countries : Outcomes and Improvement Prospects - Abadzi, Helen (World Bank, Washington, DC, 2017)
Students in lower-income countries often acquire limited literacy in school and often drop out illiterate. For those who stay, the problem is not detected until it is too late to intervene. Oral reading fluency tests given in the early grades can quickly and inexpensively assess student literacy. For this reason, one-minute reading studies have been popular. A search carried out in early 2010 showed that over 50 fluency studies have been conducted in various countries, and that norms have been established in the U.S., Mexico, and Chile. The studies often reported data in ways that were not easily comparable, and few had collected nationally representative data. However, the findings consistently showed very limited achievement. A multi-country study matching reading and instructional time data showed that the deficits are largely due to limited reading practice. The findings also suggest that few governments have taken action to improve reading outcomes on the basis of test scores. However, a number of pilot reading programs that emphasized phonics and practice were financed by donors and implemented by Non-Governmental Organizations (NGOs). These brought about substantial improvements within a few months. Their success suggests that it is eminently feasible to raise student outcomes significantly through evidence based reading methods. Overall, the oral reading fluency tests have shown good psychometric properties, although reading achievement typically shows much variability within classes and sampling procedures could improve. Cross-linguistic comparability is rough and approximate, but overall it is possible to monitor reading outcomes across time and countries.